Pengaruh Perkembangan Sastra Arab Pada Era 5.0: The Influence of the Development of Arabic Literature in the Era of 5.0 - Finanti, Adelia (An-Nahdah Al-'Arabiyah, 2024)
The emergence of the 5.0 era which began in Japan in 2019 has had a major impact on the world of literature. The development of digital-based technology has disrupted the flow of social interactions in the real world, and social interactions now only occur digitally. Social and humanitarian matters have moved to the virtual world. Research This was done to obtain straightforward information brought in by the 5.0 era. The writing was carried out to influence Arabic literature in the 5.0 era, the type of research used was literature review. In the 5.0 era, Arabic literature can influence the field of technology and innovation by stimulating creative thinking and new discoveries. Inspirational literary works can stimulate the development of new technology or encourage innovative thinking in industry. The development of Arabic literature can be a source of inspiration and knowledge for future generations. Literary works that are rich in cultural, historical and philosophical values ​​can influence the formation and development of science. Plays an important role in preserving and developing the culture and identity of the Arab nation. Arabic Literature 5.0 reflects the development of identity and social change in the Arab world. These works discuss political, social and cultural changes and provide an opportunity for writers to think about social change. Munculnya era 5.0 yang dimulai Jepang pada tahun 2019 telah memberikan dampak besar pada dunia sastra.Perkembangan teknologi berbasis digital telah mendisrupsi alur interaksi sosial di dunia nyata, dan interaksi sosial kini hanya terjadi secara digital.Yang bersifat sosial dan kemanusiaan berpindah ke dunia maya.Penelitian ini dilakukan untuk mendapatkan informasi lugas yang didatangkan pada era 5.0. Penulisan dilakukan untuk memberikan pengaruh sastra arab pada era 5.0,jenis penelitian yang digunakan adalah kajian pustaka.Di era 5.0 Sastra Arab dapat mempengaruhi bidang teknologi dan inovasi dengan merangsang pemikiran kreatif dan penemuan-penemuan baru. Karya sastra yang inspiratif dapat merangsang perkembangan teknologi baru atau mendorong pemikiran inovatif dalam industri. Perkembangan sastra Arab dapat menjadi sumber inspirasi dan pengetahuan bagi generasi mendatang. Karya sastra yang kaya akan nilai budaya, sejarah, dan filosofis dapat mempengaruhi pembentukan dan perkembangan ilmu pengetahuan. Memegang peranan penting dalam pelestarian dan pengembangan budaya dan identitas bangsa Arab.Sastra Arab 5.0 mencerminkan perkembangan identitas dan perubahan sosial di dunia Arab.Karya-karya ini membahas perubahan politik, sosial, dan budaya serta memberikan kesempatan bagi penulis untuk berpikir tentang perubahan sosial.